En el centenario de la muerte de Medardo Ángel Silva (In Memoriam) - Balseca Franco, Marcos Fernando (2019)
This text is a tribute of the Ecuadorian modernist poet Medardo Ángel Silva, in commemoration of the centennial of his death, in 2019. It highlights the different reasons why Silva is a ‘living’ poet, author of one of the most influential books in the tradition and historiography of early XXth century Ecuadorian literature, El árbol del bien y el mal (1918). It also draws attention to the return (“involution”) of the poet in the face of classicism and his achievements as a chronicler who was able to provide an account of the city’s new settings and conducts as well as processes of modernization. The author also celebrates the work and contributions of Silva’s biographer, the historian Abel Romeo Castillo, whose work and actions to keep his friend’s legacy from oblivion, were and are vital when we examine the life and writing of the Guayaquilean poet and chronicler.